Forgotten Delhi: from a heritage walker's diary - Sethi, R. S. (New Delhi Vitasta Publishing, 2009)
Delhi has been often identified with the Red Fort or the India Gate, but the history of this megalopolis is not restricted only to these famous monuments. The history of Delhi is like a beautifully woven tapestry, where the monuments and relics left behind by many of its rulers are so located that the past may be recreated to relive history. Why is the Chandni Chowk so named? What is the myth behind the shrine of Bakhtiyar Kaki? Who was Pir Ghaib and why was he so called? One may not be aware of the final resting place of Delhi's once-famous first and last woman Sultan, Razia Sultan.
Keywords: Ancient history - Delhi; IAS as an author